Impact of Sex Difference on Interaction between Adiponectin Gene Single Nucleotide Polymorphisms rs2241766, rs17300539 and rs1501299 w Environment Risk Factors of Type 2 Diabetes among the Ardabil Population in Iran - Elahe Mamashli; Farnaz Seifi Skishahr; Marefat Siahkouhian; Manouchehr Iranparvar; Asadollah Asadi; Behzad Davarnia (Journal of Ardabil University of Medical Sciences, 2021)
Background & objectives: Sex impacts the manner in which a person responds to such disease as susceptibility and progression. The aim of this study was to investigate the sex differences in the genotype distribution and allele frequency of some of the adiponectin gene polymorphisms and the comparison of the interaction of the studied polymorphisms and type 2 diabetes-related environment risk factors between males and females. Methods: This study included 103 males and 79 females with type 2 diabetes and 94 healthy males and 61 healthy females for control. Genotyping was performed using amplification refractory mutation system-PCR (T-ARMS-PCR). Statistical analysis was done using SPSS-26.0. The interaction between SNP-SNP and SNPs-environmental factors was analyzed using MDR (version 3.0.2) software. Results: Sex-genotype interaction effect was significantly associated only for triglycerides with SNP-11391G/A (p= 0.027). For SNP+45T/G, the difference genotypes were distinctly associated with hemoglobin A1c (p=0.024), body mass index (p=0.033) and body fat percentage (p=0.018). For +276G/T fasting insulin level detected a potential difference in genotypes (p=0.016). Regarding to the results of MDR analysis, the combination of fasting blood glucose, rs17300539 and sex was the best three-factor model. In this model, the distribution of patients according to sex is demonstrated that most men with GA and AA genotypes of -11391G/A had Hemoglobin A1C more than 8.5 while in women there was no relation to genotype found. Conclusion: Sexual difference impact the interaction between adiponectin gene polymorphisms and environmental risk factors. According to the findings of this study, the effect of environmental risk factors on the progression of type 2 diabetes related to Adiponectin gene polymorphisms are demonstrated within the males more than females.